MISTISISME MUDRA: RAGAM GERAKAN SPRITUALITAS DALAM DUNIA KESEHATAN - Ni Made Sinarsari; I Wayan Nerta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Mudras as mystical, ritual or symbolic gestures are practiced from a very old age in Buddhism, Hinduism and other eastern cultures. Mudras call for full body involvement performed using the fingers of both hands and hands. Each finger is associated with a special meaning and energy. The fingers have five elements namely air, water, fire, earth, sky. Mudras facilitate the harmonization of the five elements in the human body. Mudras enhance the human spirit and encourage individuals to use divine powers. Mudras in polarizing spiritual movements as emotional, devotional, psychic attitudes and aesthetics through varied movements performed regularly, the body will get amazing health benefits.